Deep Learning-Based Artistic Inheritance and Cultural Emotion Color Dissemination of Qin Opera - Yu, Han (Frontiers in Psychology, 2022)
How to enable the computer to accurately analyze the emotional information and story background of characters in Qin opera is a problem that needs to be studied. To promote the artistic inheritance and cultural emotion color dissemination of Qin opera, this paper presents an emotion analysis model of Qin opera based on attention residual network. Firstly, the neural network is improved and optimized from the perspective of model, learning rate, network layers and the network itself, and then multi head attention is added to the residual network to increase the recognition ability of the model. Finally, the model MHatt_ResNet network in this paper is obtained. The network structure can effectively identify the features of spectrogram, improve the weight information of spectrogram features, and deepen the relationship between distant information in long-time series.